Components Affecting Pharmaceutical Strategic Purchasing: A Scoping Review - Peivand Bastani; Arash Ghanbarzadegan; Soudabeh Vatankhah; Mahnaz Samadbeik (SAGE Publishing, 2019)
Pharmaceutical strategic purchasing is considered as a key to improve access to medicines especially for developing countries. The aim of this scoping review is to determine the most important components affecting pharmaceutical strategic purchasing. Here, we employed a comprehensive search strategy across PubMed, ProQuest, EBSCO, ISI Web of Science, Scopus, ScienceDirect, and Google Scholar for the terms related to medicines strategic purchasing. Among 13 included studies, 7 (53.85%) and 6 (46.15%) studies belonged to the developing and developed countries, respectively. Six main variables were emphasized as the effective variables on medicines strategic purchasing, including purchasing interventions, target group and service users, providers and suppliers of interventions, methods and motivations, price, and finally structure and organization. It seems that the insurance organizations of developing countries can achieve strategic purchasing only through the modification of the pharmaceutical pricing system and payment systems. Furthermore, they should pay attention to the real needs of target groups (demand) and modify the structure and organization as well as purchasing the most effective medicines from the best pharmaceutical providers.